Is bRaQCing bad? New roles for ribosome associated quality control factors in stress granule regulation. (16th December 2022) - Helton, Noah S.; Moon, Stephanie L.
Abstract : Maintenance of proteostasis is of utmost importance to cellular viability and relies on the coordination of many post-transcriptional processes to respond to stressful stimuli. Stress granules (SGs) are RNA–protein condensates that form after translation initiation is inhibited, such as during the integrated stress response (ISR), and may facilitate cellular adaptation to stress. The ribosome-associated quality control (RQC) pathway is a critical translation monitoring system that recognizes aberrant mRNAs encoding potentially toxic nascent peptides to target them for degradation. Both SG regulation and the RQC pathway are directly associated with translation regulation, thus it is of no surprise recent developments have demonstrated a connection between them. VCP's function in the stress activated RQC pathway, ribosome collisions activating the ISR, and the regulation of the 40S ribosomal subunit by canonical SG proteins during the RQC all connect SGs to the RQC pathway. Because mutations in genes that are involved in both SG and RQC regulation are associated with degenerative and neurological diseases, understanding the coordination and interregulation of SGs and RQC may shed light on disease mechanisms. This minireview will highlight recent advances in understanding how SGs and the RQC pathway interact in health and disease contexts.